Korelasi Spasial antara Indeks AUSMI dan WNPMI dengan Curah Hujan di Jabodetabek - Hasibuan, Muhammad Ansori; Amri, Sayful (PT. Pubsains Nur Cendekia, 2025)
The Australian Summer Monsoon Index (AUSMI) and Western North Pacific Monsoon Index (WNPMI) help analyze the relationship between zonal winds and rainfall. In Jabodetabek, rainfall is affected by monsoons, El Nino Southern Oscillation (ENSO), and Dipole Mode Index (DMI). Understanding rainfall variability helps mitigate flood and drought risks. This study evaluates the relationship between AUSMI, WNPMI, and rainfall in Jabodetabek to support monsoon-based weather prediction. The data used include 850 hPa wind data from NCEP-NCAR Reanalysis 1 and rainfall data from GPCP Monthly Analysis, processed monthly. Analysis of 850 hPa zonal winds (2000–2023) shows dominant easterlies (-1 m/s), reducing rainfall, especially in the dry season. The AUSMI index (-2.32 m/s) correlates positively (0.6) with rainfall, indicating its role in moisture transport. Meanwhile, the WNPMI index (-1.32 m/s) shows a negative correlation (-0.7), as high values bring dry air, while low values promote rain cloud formation. These indices reveal distinct monsoonal impacts on Jabodetabek's rainfall patterns.